Odpowiedzi

Najlepsza Odpowiedź!
2010-01-17T22:05:48+01:00
3x+2y=13/razy (-2)
2x+y=11/razy 3

-6x-4y=-26
6x+3y=33

-y=7
y=-7

3x+2y=13
2x+y=11/razy(-2)

3x+2y=13
-4x-2y=-22

-x=-9
x=9


b) 5x+3y=0
-x-2y=7/ razy5

5x+3y=0
-5x-10y=35

-7y=35/ :(-7)
y=-5

5x+3y=0/razy2
-x-2y=7/razy3

10x+6y=0
-3x-6y=21

7x=21/:7
x=3


c) 5=3x-y
5x-2y=7

3x-y=5/razy(-5)
5x-2y=7/razy 3

-15x+5y=-25
15x-6y=21

-y=-4
y=4

3x-y=5/razy(-2)
5x-2y=7

-6x+2y=-10
5x-2y=7

-x=-3
x=3


d) 3s+5t=-6
1,5s-2t=-3 /razy -2

3s+5t=-6
-3s+4t=6

9t=0
t=0

3s+5t=-6 / razy 2
1,5s-2t=-3 /razy 5

6s+10t=-12
7,5s-10t -15

1,5s=-27/:1,5

s=-18






8 3 8
2010-01-17T22:07:15+01:00
W zalaczniku
podpunkt b) poprawiony ( w załączniku matqq )
  • Roma
  • Community Manager
2010-01-17T22:40:03+01:00
A)
( 3x + 2y = 13
( 2x + y = 11 /*(-2)

( 3x + 2y = 13
( -4x - 2y = -22
______________
-x = -9 /*(-1)
x = 9

2x + y = 11
2*9 + y = 11
18 + y = 11
y = 11 - 18
y = -7

( x = 9
( y = -7

b)
( 5x + 3y = 0
( -x - 2y = 7 /*5

( 5x + 3y = 0
( -5x - 10y = 35
______________
-7y = 35 /:(-7)
y = -5

5x + 3y = 0
5x + 3*(-5) = 0
5x - 15 = 0
5x = 15 /:5
x = 3

( x = 3
( y = -5

c)
( 5 = 3x - y
( 5x - 2y = 7

( -3x + y = - 5 /*2
( 5x - 2y = 7

( -6x + 2y = -10
( 5x -2y = 7
_______________
-x = -3 /*(-1)
x = 3

5x - 2y = 7
5*3 - 2y = 7
15 - 2y = 7
- 2y = 7 - 15
- 2y = - 8 /:(-2)
y = 4

( x = 3
( y = 4

d)
( 3s + 5t = -6
( 1,5s - 2t = -3 /*(-2)

( 3s + 5t = -6
( -3s + 4t = 6
____________
9t = 0 /:9
t = 0

3s + 5t = -6
3s + 5*0 = -6
3s = -6 /:3
s = -2

( s = -2
( t = 0
9 3 9